Are gender differences in upper-body power generated by elite cross-country skiers augmented by increasing the intensity of exercise? - Magdalen Hegge, A.; Myhre, K.; Welde, B.; Holmberg, H. C.; Sandbakk, O. (PLOS ONE, 2015)
In the current study, we evaluated the impact of exercise intensity on gender differences in upper-body poling among cross-country skiers, as well as the associated differences in aerobic capacity, maximal strength, body composition, technique and extent of training. Eight male and eight female elite skiers, gender-matched for level of performance by FIS points, carried out a 4-min submaximal, and a 3-min and 30-sec maximal all-out test of isolated upper-body double poling on a Concept2 ski ergometer. Maximal upper-body power and strength (1RM) were determined with a pull-down exercise. In addition, body composition was assessed with a DXA scan and training during the previous six months quantified from diaries. Relative to the corresponding female values (defined as 100%), the power output produced by the men was 88%, 95% and 108% higher during the submaximal, 3-min and 30-sec tests, respectively, and peak power in the pull-down strength exercise was 118% higher (all P<0.001). During the ergometer tests the work performed per cycle by the men was 97%, 102% and 91% greater, respectively, and the men elevated their cycle rate to a greater extent at higher intensities (both P<0.01). Furthermore, men had a 61% higher VO(2)peak, 58% higher 1RM, relatively larger upper-body mass (61% vs 56%) and reported considerably more upper-body strength and endurance training (all P<0.05). In conclusion, gender differences in upper-body power among cross-country skiers augmented as the intensity of exercise increased. The gender differences observed here are greater than those reported previously for both lower-and whole-body sports and coincided with greater peak aerobic capacity and maximal upper-body strength, relatively more muscle mass in the upper-body, and more extensive training of upper-body strength and endurance among the male skiers.